Understanding the experiences of PHC nurses in caring for older patients in the post-fifth wave of the COVID-19 pandemic: an exploratory qualitative study - Ślusarska, Barbara; Nowicki, Grzegorz Józef; Chrzan-Rodak, Agnieszka; Marcinowicz, Ludmiła (Frontiers in Public Health, 2024)
Objective To ensure the best possible care, the perspective of PHC nurse work experience during the COVID-19 pandemic should be considered when developing nursing care protocols for older patients who receive PHC services. Method This exploratory qualitative study was conducted with 18 nurses working continuously in PHC between the first and fifth waves of the pandemic. Semi-structured thematic interviews were undertaken. Qualitative thematic content analysis was conducted to identify and group the themes that emerged from the discourse. Interviews were transcribed and analyzed using thematic analysis. Results The first topic describes the nurses’ experiences of physical and mental suffering in caring for older patients in response to the pandemic. The second topic covers the experience of reorganizing PHC work. The third topic focuses on the difficulties of caring for older patients. The final topic includes issues of support needs for nurses in PHC work. Conclusion The experience and understanding of PHC nurses in caring for older people during the COVID pandemic should lead to significant changes in the system of nursing care for geriatric patients and in the cooperative role within geriatric care specialist teams. Drawing on the experience of COVID-19, it is necessary to work on the weak points of PHC exposed by the pandemic in order to improve the quality of care and life for geriatric patients.